Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé